ELECTION OF NEW INSTRUCTORS FOR COMPUTER COURSES AT LKP BINA TUNAS EDUCATION USING THE MULTI ATTRIBUTE UTILITY THEORY (MAUT) METHOD - Alkarimah, Sayyida; Saprudin, Usep (Jurnal TAM (Technology Acceptance Model), 2023)
An instructor is a person whose job is to teach something and at the same time provide training and guidance, teacher, trainer, and caregiver. Among other assets such as capital, buildings, office equipment, and others, only instructors can breathe, think and behave. This uniqueness, if it has good quality and is involved in business activities, will make a big contribution to the progress of the company or institution. To obtain quality trainers who meet the expected qualifications, the company carries out a selection process in recruiting new instructors. The selection process for instructor acceptance at LKP Bina Tunas Education is carried out to determine which instructor candidates will be accepted. This research aims to select new instructor candidates more objectively because weighting can be carried out against predetermined criteria using the Multi-Attribute Utility Theory (MAUT) method. Using predetermined selection criteria, namely minimum criteria for high school graduates, experience, age, status, competence, liking challenges, and orientation. Selection of the best approach (other methods) in an effort to realize the Selection of Acceptance of Candidates for LKP Instructur Bina Tunas Education.